2014
DOI: 10.3389/fphys.2014.00020
|View full text |Cite
|
Sign up to set email alerts
|

Connexin hemichannels in the lens

Abstract: The normal function and survival of cells in the avascular lens is facilitated by intercellular communication through an extensive network of gap junctions formed predominantly by three connexins (Cx43, Cx46, and Cx50). In expression systems, these connexins can all induce hemichannel currents, but other lens proteins (e.g., pannexin1) can also induce similar currents. Hemichannel currents have been detected in isolated lens fiber cells. These hemichannels may make significant contributions to normal lens phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
65
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(65 citation statements)
references
References 106 publications
(146 reference statements)
0
65
0
Order By: Relevance
“…Pal et al found that incorporation of even a single mutant protein molecule into a gap junction in Xenopus oocytes inhibited channel function [29]. Studies of certain connexin mutants linked to congenital cataracts have implicated hemichannels with aberrant voltage-dependent gating or modulation by divalent cations in disease pathogenesis [25]. Further deletion analysis has shown that the fourth transmembrane domain (M4) and a membrane proximal region (codons 231-294) of the cytoplasmic domain are needed for transport from the endoplasmic reticulum and localization to the plasma membrane [30].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Pal et al found that incorporation of even a single mutant protein molecule into a gap junction in Xenopus oocytes inhibited channel function [29]. Studies of certain connexin mutants linked to congenital cataracts have implicated hemichannels with aberrant voltage-dependent gating or modulation by divalent cations in disease pathogenesis [25]. Further deletion analysis has shown that the fourth transmembrane domain (M4) and a membrane proximal region (codons 231-294) of the cytoplasmic domain are needed for transport from the endoplasmic reticulum and localization to the plasma membrane [30].…”
Section: Discussionmentioning
confidence: 97%
“…Gap junctions are membrane specializations that contain clusters of intercellular channels that are permeable to ions and small solutes, including ions (K+, Ca2+), nutrients, small metabolites (e.g. glucose), and second messengers (inositol triphosphate, cAMP, cGMP) (≤1 kDa) [25]. These functions play a critical role in lens metabolic homeostasis and maintenance of transparency of fibers within the ocular lens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the required diffusion time would be too long to explain a response in epithelium that is detectable at 1 min. We also considered the possibility that because cells throughout the fiber mass as well as the epithelium are functionally coupled (Bassnett et al, 1994; Beyer and Berthoud, 2014; Mathias et al, 2007), depolarization caused by damage at the posterior pole might have an immediate influence on the remainder of the lens. However, a depolarization-mediated response is not consistent with the ability of HC067047 to prevent SFK response.…”
Section: Discussionmentioning
confidence: 99%
“…Connexins form intercellular channels that facilitate the circulation of water, ions and solutes within the avascular lens (Mathias et al, 2010). They can also form “hemichannels” connecting the cytoplasm and extracellular space (Beyer and Berthoud, 2014). …”
Section: Introductionmentioning
confidence: 99%